Management factors associated with mortality of dairy calves in Finland: A cross sectional study. (October 2016) - Seppä-Lassila, L.; Sarjokari, K.; Hovinen, M.; Soveri, T.; Norring, M.
Highlights: Mortality of dairy calves in Finland was evaluated in relation to farm management. Mortality of calves was higher in herds of larger size. Lower herd average milk production was associated with higher calf mortality. Longer periods of whole milk feeding and separation of sick from healthy calves were associated with lower mortality. Farmers can reduce calf mortality by applying appropriate management practices. Abstract: Mortality at herd level is an indicator of overall calf welfare on dairy farms. The aim of this cross sectional study was to identify management factors associated with calf mortality on dairy farms in Finland. Calf mortality data and information on management practices collected during farm visits and farmer interviews were analysed using linear models. The average size of 82 herds enrolled in the study was 125 ± 41 cows. The mortality risk of calves <7 days of age was 5 (or 5.2) ± 2.3% and was associated with larger herd size and the practice of not separating sick calves from other calves (6.0 ± 0.4 vs. 4.7 ± 0.3%; P < 0.05). The mortality risk of calves aged 7–180 days was 6 (or 5.7) ± 6.2% and increased with a shorter whole milk feeding period, longer period in the calving pen and lower average herd production level ( P < 0.05). The mortality risk of calves was lower on farms where a veterinarian disbudded calves instead of farmer. Longer milk feeding and improved management of sick calves are recommended to reduce calf mortality. Specific management practices associated with lower mortality risk should be emphasised when advising farmers on how to enhance calf welfare.